First genome assembly and annotation of Sanghuangporus weigelae uncovers its medicinal functions, metabolic pathways, and evolution - Jin, Can; Ma, Jin-Xin; Wang, Hao; Tang, Lu-Xin; Ye, Yi-Fan; Li, Xin; Si, Jing (Frontiers in Cellular and Infection Microbiology, 2024)
Sanghuangporus, also known as “Sanghuang” in China, is a well-known genus of traditional Chinese medicinal macrofungi. To make more effective use of Sanghuangporus resources, we completed the first genome assembly and annotation of a monokaryon strain of S. weigelae in the present study. A 33.96-Mb genome sequence was assembled as 13 contigs, leading to prediction of 9377 protein-coding genes. Phylogenetic and average nucleotide identity analyses indicated that the S. weigelae genome is closely related to those of other Sanghuangporus species in evolutionary tree, which clustered in one clade. Collinearity analysis revealed a high level of collinearity of S. weigelae with S. baumii, S. vaninii, and S. sanghuang. Biosynthesis pathways potentially involved in medicinal properties, including terpenoid and polysaccharide synthesis, were identified in S. weigelae, while polysaccharides were identified as the main medicinal metabolites in S. weigelae, with flavonoids more important in Sanghuangporus than other medicinal mushroom groups. Genes encoding 332 carbohydrate-active enzymes were identified in the S. weigelae genome, including major glycoside hydrolases and glycosyltransferases predicted, revealing the robust lignocellulose degradation capacity of S. weigelae. Further, 130 genes, clustered in seven classes were annotated to encode cytochromes P450 in the S. weigelae genome. Overall, our results reveal the remarkably medicinal capacity of S. weigelae and provide new insights that will inform the study of evolution and medicinal application of S. weigelae. The data are a reference resource for the formulation of scientific and rational ecological protection policies for Sanghuangporus species.